Oxidative stress-mediated memory impairment during aging and its therapeutic intervention by natural bioactive compounds - Singh, Padmanabh; Barman, Bhabotosh; Thakur, Mahendra Kumar (Frontiers in Aging Neuroscience, 2022)
Aging and associated neurodegenerative diseases are accompanied by the decline of several brain functions including cognitive abilities. Progressive deleterious changes at biochemical and physiological levels lead to generation of oxidative stress, accumulation of protein aggregates, mitochondrial dysfunctions, loss of synaptic connections, and ultimately neurodegeneration and cognitive decline during aging. Oxidative stress that arises due to an imbalance between the rates of production and elimination of free radicles is the key factor for age-associated neurodegeneration and cognitive decline. Due to high energy demand, the brain is more susceptible to free radicals-mediated damages as they oxidize lipids, proteins, and nucleic acids, thereby causing an imbalance in the homeostasis of the aging brain. Animal, as well as human subject studies, showed that, with almost no or few side effects, dietary interventions and plant-derived bioactive compounds could be beneficial to recovering memory or delay the onset of memory impairment. As the plant-derived bioactive compounds have antioxidative properties, several of them were used to recover the oxidative stress-mediated changes in the aging brain. In the present article, we review different aspects of oxidative stress-mediated cognitive change during aging and its therapeutic intervention by natural bioactive compounds.